Pengaruh Akuntabilitas, Gaya Kepemimpinan, Kompetensi dan di Mediasi Motivasi Terhadap Kinerja Organisasi - Isma Arum Wardiana; Suwardi Bambang Hermanto (Department of Accounting-Faculty of Economic and Business (FEB), 2019)
This research aimed to find out the effect of accountability, leadership style, competency and motivation on the organization performance, especially in government organization, Sidoarjo. The data collection thecnique used simple random sampling. Furthermore, there were 111 respondents as sample in 34 village area, Sidoarjo. Moreover, the data analysis thecnique used PLS (Partial Least Square. The research result concluded the transformasional leadership style had positive effect on the performance and motivation of managerial porformance. Furthermore, the managerial ownership had positive effect on the motivation managerial work. Furthermore, this research had correlated with the government support to create a good governance.